lecture_17 (dragged)

# lecture_17 (dragged) - MA 36600 LECTURE NOTES WEDNESDAY...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: MA 36600 LECTURE NOTES: WEDNESDAY, FEBRUARY 25 Complex Roots Euler’s Formula. We showed in the previous lecture that eit = cos t + i sin t. This is known as Euler’s Formula. In general, if we write r = λ + iµ in terms of real numbers λ and µ, we have the expression ert = eλt · eiµt = eλt (cos µt + i sin µt) = eλt cos µt + i eλt sin µt. In fact, because we have the Taylor Series expansion ∞ ￿ rk ert = tk =⇒ k! d ￿ rt ￿ e = r ert dt k=0 for any complex number r. Hence we can always make sense of the function y (t) = ert as a solution to a homogeneous linear diﬀerential equation with constant coeﬃcients. Example. We explain how to ﬁnd the general solution to the diﬀerential equation y ￿￿ + 9 y = 0. We guess a solution in the form y (t) = ert so that we have the characteristic equation r2 + 9 = 0 Hence the general solution is the function =⇒ r = ±3 i. y (t) = a1 e3i + a2 e−3i = a1 (cos 3t + i sin 3t) + a2 (cos 3t − i sin 3t) = c1 cos 3t + c2 sin 3t in terms of the constants c1 = a1 + a2 and c2 = i a1 − i a2 . Review. Consider the constant coeﬃcient second order diﬀerential equation a y ￿￿ + b y ￿ + c y = 0. Recall that it has the associated characteristic equation a r2 + b r + c = 0. We assume that b2 − 4 a c < 0 so that we have complex roots. We may write these complex roots as ￿ r1 = λ + i µ |b2 − 4 a c| b in terms of λ=− , µ= . r2 = λ − i µ 2a 2a We saw in the previous lecture that we have the expression er1 t = eλt · eiµt = eλt (cos µt + i sin µt) = eλt cos µt + i eλt sin µt; . er2 t = eλt · e−iµt = eλt (cos µt − i sin µt) = eλt cos µt − i eλt sin µt Both expressions follow from Euler’s Formula eit = cos t + i sin t. In particular, we may write the general solution to the diﬀerential equation as y (t) = a1 er1 t + a2 er2 t = c1 eλt cos µt + c2 eλt sin µt in terms of the constants c1 = a1 + a2 and 1 c2 = i a1 − i a2 . ...
View Full Document

## This note was uploaded on 11/30/2011 for the course MATH 366 taught by Professor Edraygoins during the Spring '09 term at Purdue.

Ask a homework question - tutors are online